Evidencing size-dependent cooperative effects on spin crossover nanoparticles following their HS→LS relaxation. Issue 46 (14th November 2018) - Delgado, Teresa; Enachescu, Cristian; Tissot, Antoine; Hauser, Andreas; Guénée, Laure; Besnard, Céline
Abstract : The size dependence of the relaxation mechanism after photo-excitation through the Light-Induced Excited Spin-State Trapping (LIESST) effect of [Fe(pz)Pt(CN)4 ] micro- and nanoparticles is evidenced experimentally and simulated in the framework of the mechanoelastic model. Abstract : The HS→LS relaxation at cryogenic temperatures after photo-excitation through the light-induced excited spin-state trapping (LIESST) effect of the [Fe(pz)Pt(CN)4 ] micro- and nanoparticles is probed by optical-absorption spectroscopy and X-Ray Powder Diffraction (XRPD) using synchrotron radiation. A size dependence of the relaxation mechanism is evidenced, due to the inhibition of cluster formation for smaller size particles. This result is explained by simulations performed in the frame of the mechanoelastic model.